Range Shifts of the Endangered Luehdorfia chinensis chinensis (Lepidoptera, Papilionidae) and Its Specific Hosts in China Under Climate Change - Ze Lan; Guangfu Zhang (Ecology and Evolution)
ABSTRACT Luehdorfia chinensis chinensis, endemic to China, is an endangered, rare, and protected butterfly with high host specificity. However, little is known about how this butterfly and its host plants respond to climate change. In this study, we built ensemble models in the Biomod2 platform to predict the potential distributions of L. c. chinensis and its two host plants, identify key environmental factors, and calculate the niche overlaps between them. The results showed that under the current climate, L. c. chinensis covered a suitable area of approximately 1,146,520 km2, accounting for 11.95% of China's total territory, and was primarily distributed in central and southeastern China. Precipitation of the driest quarter was identified as the primary factor influencing the distribution of L. c. chinensis, whereas precipitation‐related variables were the primary factors influencing the distributions of both host plants. Under future climate scenarios, the butterfly is projected to increase slightly in suitable habitat, while the two hosts show contrasting trends in range shift and niche overlap. Our findings indicate that climate change not only alters the extent and integrity of suitable habitats of the butterfly and its hosts but also affects its larval host choice. Therefore, it is essential to take into account the suitable habitats of the endangered butterfly and its hosts when developing climate‐adapted conservation strategies.